Manajemen Pendidikan Dasar : Apakah Sistem Sentralisasi Ataukah Desentralisasi: Suatu Kajian SD al-Anwar Kota Pasuruan - Shodiq, Abdulloh (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
The issue of decentralization refers to the extent to which authority has been delegated, authority from one level of management to the next level of management that is below it, while centralization is the opposite or remains held at the top level. The issue here is not whether an organization must decentralize, but to what extent it is decentralized. For example, basic education management tends towards centralization or decentralization. Let's take the example of the case of basic education management in Indonesia, including a private elementary school, namely SD Al-Anwar, Pasuruan City